A cytochrome P450 gene plays a role in the recognition of sex pheromones in the tobacco cutworm, Spodoptera litura. Issue 4 (8th April 2017) - Feng, B.; Zheng, K.; Li, C.; Guo, Q.; Du, Y.
Abstract: Cytochrome P450 (P450 or CYP) genes are involved in fundamental physiological functions, and might be also associated with the olfactory recognition of sex pheromones in beetles and moths. A P450 gene, Spodoptera litura CYP4L4 ( SlituCYP4L4 ), was cloned for the first time from the antennae of S. litura . SlituCYP4L4 was almost exclusively expressed in the adult stage and predominantly expressed in the adult antennae. In situ hybridization showed that SlituCYP4L4 localized mainly at the base of the long sensilla trichoidea, which responds to sex pheromone components. Pretreatment with an S. litura sex pheromone significantly reduced the expression levels of SlituCYP4L4, consistent with other genes involved in sex pheromone recognition. The expression level of SlituCYP4L4 was different in moths collected with different ratios of sex pheromone lures and collected in different geographical locations. After gene knockdown of SlituCYP4L4 in the antennae, the electroantennogram (EAG) responses of male and female moths to (9Z, 11E)‐tetradecadienyl acetate or (9Z, 12E)‐tetradecadienyl acetate were significantly decreased. In contrast, EAG responses to plant volatiles and sex pheromones of other moth species were not significantly influenced in these moths. SlituCYP4L4 was also expressed in the gustatory tissues and sensilla, which suggests that SlituCYP4L4 may have other functions in the chemosensory system. Our results have shown for the first time the function of a CYP gene with appendage‐specific expression in insect sex pheromone recognition, especially in adult moths.